SENI LUKIS MIXEDMEDIA: Karya Mahasiswa Program Studi Pendidikan Seni Rupa Fakultas Seni dan Desain Universitas Negeri Makassar - Yabu M. Yabu M.; Benny Subiantoro; Achmad Yasin (Universitas Negeri makassar, 2019)
This research is qualitative descriptive research aimed to describe: (1) strategy used by lecturers in developing creative imagination of students of Art Education Study Program of Faculty of Arts and Design of Universitas Negeri Makassar through Development of Mixedmedia painting; (2) understanding of students in realizing mixed media painting. Population and sample in this research were all works made by students participating in the painting III courses in Art Education Program in the odd semester of the academic year 2015/2016. The object in this research was the work result of student experimentation in the task of Artist III course, there were 40 works to be analyzed. The technique of data collection was done through observation using observation format, documentation of work, and limited interview. The collected data was analyzed by descriptive-qualitative analysis technique. The results showed that: (1) the students' creative imagination can be fostered through gradually mixed media painting tasks; (2) generally, the students of Art Painting III have a good understanding of creating mixed painting with media utilizing various mixed materials.